Experimental Investigation of Non-Premixed Combustion Process in a Swirl Burner with LPG and Hydrogen Mixture - Abay Mukhamediyarovich Dostiyarov; Dias Raybekovich Umyshev; Andrey Anatolievich Kibarin; Ayaulym Konusbekovna Yamanbekova; Musagul Elekenovich Tumanov; Gulzira Ainadinovna Koldassova; Maxat Arganatovich Anuarbekov (Energies, 2024)
In the modern world, issues related to the use of alternative fuels are becoming increasingly pressing. These fuels offer the potential to achieve significantly improved environmental and technological performance. Currently, among such fuels, biodiesel, ammonia, LPG, and hydrogen are considered the most promising options. LPG and hydrogen exhibit a high Lower Heating Value (LHV) and have a relatively low environmental impact. This article investigates the combustion of hydrogen-LPG mixtures in a diffusion burner. The main parameters under study include the proportion of hydrogen in the fuel, equivalence ratio, and vane angle. The analyzed parameters encompass NOx and CO concentrations. The studies have demonstrated that the addition of hydrogen can reduce greenhouse gas emissions, as the combustion product is clean water. The primary focus of this research is the examination of combustion processes involving flow swirl systems and alternative fuels and their mixtures. The studies indicate that flame stabilization is significantly influenced by several factors. The first factor is the amount of hydrogen added to the fuel mixture. The second factor is the degree of mixing between the fuel and oxidizer, along with hydrogen. Lastly, the equivalence ratio plays a crucial role. As the studies have shown, the maximum stabilization for a speed of 5 m/s is achieved at an angle of 60° and a hydrogen fraction of 40%, resulting in φLBO = 0.9. This represents an 8.0% improvement in stabilization compared to the baseline mode, primarily due to the substantial proportion of hydrogen. An analysis of flame photographs reveals that as the twist angle increases, a recirculation zone becomes more apparent. Increasing the blade angle and incorporating hydrogen leads to a reduction in CO concentrations in the exhaust gases. The analysis indicates that increasing the hydrogen proportion to 50%, compared to the absence of hydrogen, results in a 30% decrease in CO concentration. In our case, for the option φ = 0.3 and blade angles of 60°, the reduction in CO concentration was 28.5%. From the authors’ perspective, the most optimal vane angle is 45°, along with a hydrogen fraction of 30–40%. With these parameters, it was possible to achieve concentrations of NOx = 17–25 ppm, φLBO = 0.66, and CO = 130–122 ppm.